MODEL LATIHAN IMAGERY SEBAGAI PENDUKUNG KETEPATAN WAKTU PENCAK SILAT KATEGORI TUNGGAL, GANDA DAN REGU - bayu iswana (Indonesian Journal Of Educational Research and Review, 2018)
This study aims to produce a model of imagery training as a support for the timeliness, of pencak silat in the category of single, double, team (TGR). The method in this study is Research and Development that produces imagery models in the user guide for Special Cognitive Practices, Motivational Specific, Motivational General Arosual, Motivational General. Subjects were coach and single, double, and team kategories PPLD pencak silat Musi Banyuasin regency, South Sumatra Province. The research design used in this study was 1, potential problems, 2 data collection, 3 product designs, 4 design validations, 5 design revisions, 6 small product trials, 7 product revisions, 8 large product trials, 9 product revisions, 10 products mass. Validation was carried out on several martial arts experts who had National certificates, both referees and trainers. The results of the study show that experts give an 80% assessment of all product drafts that are validated and tested. This shows that the imagery training model products support the timeliness of pencak silat single, double and team category can be used as an effective exercise model